TMIC-73. HIGH-DIMENSIONAL HISTOPATHOLOGIC EVALUATION OF THE HYPOXIC MICROENVIRONMENT IN GLIOBLASTOMA. (14th November 2022) - Mansouri, Sheila; Zaidi, Mark; Singh, Olivia; Ali, Hafsah; Karimi, Shirin; Lombard, Phoebe; Dvorkin-Gheva, Anna; Velasquez, Carlos; Devaraja, Kaviya; Sosa, Julio; Patil, Vikas; Wei, Qingxia; et al.
Abstract: Rapidly growing solid tumors such as glioblastoma (GBM) are characteristically hypoxic, displaying large areas of necrosis surrounded by hyperproliferative pseudopalisading cells. Intra-tumoral hypoxia develops over time in the three-dimensional space and the degree of tissue oxygenation is a dynamic process that varies continuously. Combined with the extensive inter- and intra-tumoral heterogeneity associated with GBM at the bulk and single cell level, hypoxia contributes to a gradient of molecular alterations that are specific to the different cell populations that make up the bulk of the tumor and reside in specific niches. To date, high dimensional histopathologic analyses of the hypoxic regions within GBM tissue have not been performed. Here, we took a combined spatial and single-cell proteomic profiling approach to investigate the histopathologic features of hypoxia by leveraging a unique clinical study where the exogenous hypoxia marker pimonidazole (PIMO) is administered to patients with GBM prior to surgery. Tissue specimens were subjected to imaging mass cytometry and serial immunohistochemistry using a panel of 27 markers associated with cellular hallmarks of hypoxia, metabolism, proliferation, stemness, angiogenesis, and immune cell types. We took high-resolution imaging and statistical approaches to explore the interplay of the different markers within hypoxic regions of primary and recurrent GBMs, in addition to IDH -mutant gliomas. Our findings elucidate the expression pattern of key biological markers relative to one another, altered composition of different cell types, along with differential proliferative, transcriptional, and translational activation states associated with each cell type within the hypoxic regions of GBM.